STUDI ANALISIS DAYA DUKUNG TIANG BETON DENGAN MENGGUNAKAN DATA GETARAN - M Alhimni Rusdi M Alhimni Rusdi (UNIB Press, 2022)
Abstract: The foundation is a very important structural element considering its function, and it is necessary to know the strength of its bearing capacity. This study aims to determine the bearing capacity of the installed foundation using vibration data based on low strain and the tool used is called a 3-axis accelerometer. In this study, what is meant by carrying capacity is Pcr (critical load/bending load), which is precisely when the concrete experiences the first crack. There are 2 variations of concrete test objects ini this study : plain concrete and reinforced concrete with a size of 20 cm x 20 cm x 100 cm. The test object is planted in the soil as deep as 90 cm, after which it is anchored by a tool called the 3-axis accelerometer, then given several variations of the load so that the test can be carried out. After testing, the vibration data will be converted to the frequency domain, then the natural frequency will be plotted into a linear curve along with the applied load so that the Pcr value of the concrete pile is obtained. After that, the Pcr value obtained will be compared with the SAP 2000 modeling as proof. The results of this study showed that the deviation between the Pcr value with the experimental method and the SAP 2000 modeling Pcr value was 0.22% in plain concrete, and 1.10% in reinforced concrete. This proves that the bearing capacity of concrete piles (Pcr) can be known accurately by using vibration data.